Fair-weather potential gradient and its coupling with ionospheric potential from three Antarctic stations: Case studies. (March 2019) - Victor, N.Jeni; Siingh, Devendraa; Panneerselvam, C.; Elango, P.; Samy, V.S.
Abstract: Simultaneous measurements of potential gradient (PG) from Antarctica stations, Vostok (78° 27′ S, 106° 52′ E), Dome C (75° 06′ S, 123° 20′ E) and Maitri (70° 45′ S, 11°44′ E) during magnetically disturbed days under fair-weather conditions are discussed. An attempt has been made to study the influence of solar wind-magnetosphere interaction on PG. During magnetic daytime (0600–1800 UT), linear relation between ΔPG and associated ionospheric potential from Dome C and Vostok are observed. The liner response is poor during the magnetic night time (1800-0600 UT). This trend has been addressed by the sun-aligned two-cell plasma convection flow and its differential motion over the stations. It is found that linear relation decreased when negative convection pattern moves towards, overhead and away from the stations under dawnward motion of plasma (IMF By < 0). In addition, the ionospheric potential at dusk sector modulated the PG if the plasma flow remained stable for more than 1 h. The results further showed that the scale size factor between ionospheric potential and PG may influence up to some extent in coupling efficiency. Month-wise Fair-weather PG pattern effectively accounts the ambient PG variation. Highlights: Simultaneous observations of PG from Vostok, Dome C and Maitri are presented. Response of PG has been addressed by the motion of plasma convection pattern. Ionospheric potential at dusk side modulated the PG on stable plasma flow. Fair-weather PG pattern effectively accounts the background PG variation.